The ELI-ALPS facility: the next generation of attosecond sources. (13th June 2017) - Kühn, Sergei; Dumergue, Mathieu; Kahaly, Subhendu; Mondal, Sudipta; Füle, Miklós; Csizmadia, Tamás; Farkas, Balázs; Major, Balázs; Várallyay, Zoltán; Calegari, Francesca; Devetta, Michele; Frassetto, Fabio; et al.
Abstract: This review presents the technological infrastructure that will be available at the Extreme Light Infrastructure Attosecond Light Pulse Source (ELI-ALPS) international facility. ELI-ALPS will offer to the international scientific community ultrashort pulses in the femtosecond and attosecond domain for time-resolved investigations with unprecedented levels of high quality characteristics. The laser sources and the attosecond beamlines available at the facility will make attosecond technology accessible for scientists lacking access to these novel tools. Time-resolved investigation of systems of increasing complexity is envisaged using the end stations that will be provided at the facility.